2021
DOI: 10.2147/imcrj.s321547
|View full text |Cite
|
Sign up to set email alerts
|

Scrotal Abscess in a Japanese Patient Caused by Prevotella bivia and Streptococcus agalactiae, Successfully Treated with Cefazolin and Amoxicillin: A Case Report

Abstract: Background: Infections caused by Prevotella bivia, a gram-negative anaerobic bacillus, are rare, with no reported cases in Japan. We present a novel case of scrotal abscess in a Japanese patient co-infected with Prevotella bivia and Streptococcus agalactiae. Case Presentation: A 41-year-old uncontrolled diabetic man complained of swelling and pain in the scrotum. On examination, computed tomography revealed an abscess of 5-cm diameter in the scrotum. Then, the abscess was incised and drained. He was treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In a systematic review of case rereports of P bivia infections, 19 cases were reported by 2021. Co-infection with other microorganisms was reported in seven cases and abscess occurred in seven of the 19 cases [6] . Thus, P bivia is predisposed to cause co-infection and form abscess.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In a systematic review of case rereports of P bivia infections, 19 cases were reported by 2021. Co-infection with other microorganisms was reported in seven cases and abscess occurred in seven of the 19 cases [6] . Thus, P bivia is predisposed to cause co-infection and form abscess.…”
Section: Discussionmentioning
confidence: 92%
“…Co-infection with other microorganisms was reported in seven cases and abscess occurred in seven of the 19 cases. [ 6 ] Thus, P bivia is predisposed to cause co-infection and form abscess. Some researchers have envisioned three bacterial/SARS-CoV-2 co-infections scenarios: (1) secondary SARS-CoV-2 infection following bacterial infection/colonization; (2) combined viral/bacterial pneumonia; and (3) secondary bacterial “superinfection” after SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Rare infections associated with Prevotella species include abscesses of the head and neck, otitis media, sinusitis, aspiration pneumonia, female genital tract infections, and intraabdominal infections [ 6 ]. Prevotella bivia is a rare cause of infection in the literature, with only 18 documented cases of infection globally, and the optimal antibiotic regimen reported from those cases varies widely [ 7 ]. Many of the cases were treated with multiple courses of different antibiotics, demonstrating the difficulty of properly treating infections caused by Prevotella bivia .…”
Section: Discussionmentioning
confidence: 99%
“…A common error in the management of nonpuerperal breast abscess is treatment with narrow-spectrum gram-positive antibiotics. This strategy excludes anaerobes, which contribute to a significant proportion of nonpuerperal breast abscesses, and may be a contributing factor in the high recurrence rates noted with such abscesses [ 7 ]. Consideration should be made for treatment with broad-spectrum antibiotics which target anaerobic and gram-positive bacteria, such as amoxicillin-clavulanate, or clindamycin.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy individuals, Prevotella can cause pelvic infections and genital tract, chest wall, and breast abscesses. 4,5 Reports of Prevotella isolated and identified from infected sites in patients with WAS are lacking. Susceptibility to infection and closed space, created by ointment application in this case, is likely to have created an environment conducive to the growth of anaerobic bacteria; patients may present with prolonged skin lesions following BCG vaccination.…”
mentioning
confidence: 99%